Gambaran Motivasi Berprestasi Remaja yang Mengalami Dampak Broken Home di Komunitas Rese Sengkol, Tangerang Selatan - Dimas Noto Kusumo; Moh. Amin Tohari (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
This article aims to analyze and describe the achievement motivation of adolescents affected by broken homes in the Rese Sengkol Community. This research uses a qualitative approach with data collection in the form of interviews, observations and documentation studies. The results showed that achievement motivation is important for every individual, to achieve their goals and develop their potential. Motivation can come from the family, because one of the functions of the family is to support the morale of its members to achieve, but not all individuals get this. Broken home family situations are one of the causes, broken homes experienced include life separation and death separation, the factors vary, ranging from house separation, economic factors, to unstable emotions from parents. The impact of broken homes experienced by adolescents is not only negative, such as vulnerable psychological conditions, they put this aside with a supportive community environment. The positive impacts of broken homes include becoming independent, mature, and able to adjust. Achievement motivation is illustrated by the existence of factors that influence adolescent achievement motivation including the figures and characteristics of the models they admire, parental expectations, environmental support, and independent parenting. As a community that focuses on the arts. The implementation of achievement motivation in this community is reflected in the paintings and drawings that are exhibited in art exhibitions.